A evolução do lítio em estrelas do tipo-solar através do diagrama HR - Barros, Sumaia Sales Vieira de (2007)
Important advances have been made along the last decade in the study of the lithium behavior in solar-type stars. Among the most important discoveries what attracts attention is that the distribution of lithium abundance in the late F-type giant stars tends to be discontinuous, at the same time of a sudden decline in rotation and a gradual decline according to the temperature for giant red stars of such spectral type. Other studies have also shown that synchronized binary systems with evolved components seem to keep more of their original lithium than the unsynchronized systems. evertheless, the connection between rotation and lithium abundance as well as the role of tidal effects on lithium dilution seem to be more complicated matters, depending on mass, metallicity and age. This work brings an unprecedented study about the behavior of lithium abundance in solartype evolved stars based on an unique sample of 1067 subgiant, giant and supergiant stars, 236 of them presenting spectroscopic binary characteristics, with precise lithium abundance and projected rotational speed. Now the lithium-rotation connection for single and binary evolved stars is analyzed taking into account the role of mass and stellar age